All About Feelings? Emotional Appeals as Drivers of User Engagement With Facebook Posts - Bil-Jaruzelska, Anna (2022)
Political campaigns routinely appeal to citizens’ emotions, and there is evidence that such appeals influence political behaviour. Social media, an important arena through which political actors communicate with voters, provide a rich source of data for investigating not only which communication strategies they use but also which of these engage followers. Building on political psychology and political communication literature, the present study investigates the relationship between appeals to specific emotions (fear, anger, enthusiasm, and pride) and the engagement that such posts generate on Facebook. We created an engagement index sensitive to the Facebook page follower count and employed multilevel modelling techniques. We conducted a manual content analysis of posts by British political parties and their leaders (N = 1,203) during the Brexit referendum debate on Facebook. We found that engagement with a post substantially increases when appeals to anger, enthusiasm, and pride are present. Conversely, there is no relationship between appeals to fear and engagement. Thus, the results indicate with observational data what we know about the effects of emotions from experimental research in political psychology. Emotions of the same valence (e.g., fear and anger) have a different relationship with user engagement and, by extension, political behaviour and participation online. This indicates that to fully understand the role of emotions in generating user engagement on Facebook, we must go beyond the positive and negative dichotomy and look at discrete emotions. Lastly, British political actors used Facebook communication to generate online political participation during the Brexit debate.